MENTAL HEALTH SUPPORT SYSTEMS IN HYBRID LEARNING ENVIRONMENTS IN 2023: ADDRESSING POST-PANDEMIC STUDENT AND EDUCATOR WELL-BEING - Dutta, Banti (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The COVID-19 pandemic accelerated the widespread adoption of hybrid learning models, reshaping educational practices in ways that continue to affect students and educators in 2023. While hybrid environments offer flexibility and increased accessibility, they also introduce unique stressors that contribute to mental health challenges, including digital fatigue, isolation, and blurred boundaries between academic and personal life. This study examines the mental health implications of hybrid learning for both students and educators, with particular attention to the effectiveness of institutional support systems. Employing a qualitative research design, data were collected through semi-structured interviews, focus groups, and document review to capture lived experiences and perceptions of well-being. Thematic analysis revealed several recurring challenges: students reported difficulties with motivation, belonging, and equitable access to digital resources, while educators highlighted increased workload, technological anxiety, and emotional labor. Although institutions expanded online counseling and wellness initiatives, these supports were found to be inconsistent and disproportionately student-focused. The findings underscore the need for holistic and sustainable approaches to mental health that integrate systemic support for both students and educators. Ultimately, the study concludes that prioritizing well-being is essential for the long-term success and equity of hybrid learning environments.